2011
DOI: 10.1097/hjh.0b013e328342c8f7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atorvastatin among older and younger patients in the Anglo-Scandinavian Cardiac Outcomes Trial Lipid-Lowering Arm

Abstract: Atorvastatin reduced the risk of major cardiovascular events to a similar relative extent in both older and younger patients with treated hypertension. However, given that event rates were higher in older patients, the absolute benefits of atorvastatin were greater for older than younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…The MEGA trial found a 33% risk reduction for coronary heart disease with no increase in non-cardiovascular disease mortality or other adverse events, and this effect was independent of age up to 80 8. The ASCOT-LLA trial (in patients aged 40-79) found that statins reduce the risk of cardiovascular disease events and procedures (including fatal and non-fatal stroke),9 and this effect was again independent of age 37. The PROSPER trial, however, showed that while pravastatin given for three years reduced the risk of coronary disease in elderly individuals (aged 70-82), it had no effect on the risk of stroke 38…”
Section: Discussionmentioning
confidence: 99%
“…The MEGA trial found a 33% risk reduction for coronary heart disease with no increase in non-cardiovascular disease mortality or other adverse events, and this effect was independent of age up to 80 8. The ASCOT-LLA trial (in patients aged 40-79) found that statins reduce the risk of cardiovascular disease events and procedures (including fatal and non-fatal stroke),9 and this effect was again independent of age 37. The PROSPER trial, however, showed that while pravastatin given for three years reduced the risk of coronary disease in elderly individuals (aged 70-82), it had no effect on the risk of stroke 38…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-nine RCTs were extracted from these studies, while the updated search for recent RCTs retrieved 387 records. After applying our study inclusion criteria, a total of eight trials [33][34][35][36][37][38][39][40] were eligible for our meta-analysis. Two trials focused on elderly subjects, and six trials comprised subgroup analyses of elderly subjects.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Previous studies have indicated the benefit from lipid lowering, in almost every analysis and for almost every outcome 11,12. In the elderly population, hypercholesterolemia may be the only major CVD risk factor13,14 or one out of several major risk factors 15,16. Lipids tend to change while we age, altering the risk of CVD 17,18.…”
Section: Introductionmentioning
confidence: 99%